MEMORY TYPE FLOATING CONTROL CHARTS FOR MONITORING PROCESS COEFFICIENT OF VARIATION (Contemporary Journal of Social Science Review, 2025)
This Paper aims to create a new floating exponentially weighted moving average control chart and monitor the coefficient of variation by using a variable sample size technique. It can be built using a log transformation, and Monte Carlo simulations with various shift sizes can be used to study it. Average run lengths of ARL 250, 370, and 500 are used with shift size at n = 5, 8, and 12 to suggest a new CV floating EWMA control chart. The findings show that for various values of n, the recently proposed CV floating EWMA control chart coefficient of variation outline performs well as the shift sizes rise. Comparing this new CV floating EWMA control chart to the current coefficient of variation control chart, it is evident that the new proposed CV floating EWMA control chart yields superior outcomes. A practical example of the die casting hot chamber process, which produces zinc alloy for the sanitary industry, is also provided.